Proposal for a Directive of the European Parliament and of the Council on Soil Monitoring and Resilience (Soil Monitoring Directive) of 5 July 2023 in the Context of the Right to Health, Food and Information Concerning the Environment .......... 169 - Suchoń, Aneta (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
The objectives of this chapter are: firstly, to determine whether the regulatory framework contained in the draft Soil Monitoring Directive of 5 July 2023, in particular, with regard to healthy soils, can contribute to human health, food and soil information (also of global relevance under the Charter of Fundamental Rights); and secondly, to identify selected legal instruments under the CAP 2023-2027 and other soil health regulations. Reference will also be made to case law. At the same time, soils, which are important for human health and life, need to be taken into account in other EU policies, e.g. agriculture, energy, regional policy. First, comments on the importance of healthy soils, FAO studies, and EU initiatives on soils are presented. The section that follows presents selected elements from the draft Directive such as Soil Health Monitoring, Soil Health Assessment, Soil Health Certification, Sustainable Soil Management, Identification of potentially contaminated sites, and EU funding. It is pointed out that the draft Directive provides for access to a review procedure before a court of law or another independent and impartial body established by law to challenge the substantive or procedural legality of soil health assessments, of measures taken under this Directive and of any failure of competent authorities to act. In the conclusion, the author provides a positive assessment of the draft (Soil Monitoring Directive) of 5 July 2023. At the same time, some elements may cause problems, for example, in relation to land ownership and data sharing on private land. An important step will therefore be to transpose the principles of the Soil Monitoring Directive into national legislation and to take into account other EU and national legislation.